2009
DOI: 10.2503/jjshs1.78.224
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Exposure of Mother Plants to Low Temperatures Delays Flowering of Japanese Autumn-flowering Chrysanthemum morifolium Ramat. ‘Jinba’ and ‘Seiko no Aki’

Abstract: To clarify the reason for delayed flowering of Chrysanthemum morifolium 'Jinba' cuttings propagated from mother plants during winter and spring production, the effects of growing temperatures of mother plants, and those of rooted cuttings grown in long days or short days, on vegetative growth and flowering in three autumnflowering Chrysanthemum cultivars were investigated. Rooted cuttings of 'Jinba', propagated from mother plants exposed to two temperature regimes, were planted on December 26 and grown in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2009
2009
2009
2009

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…However, in the autumn-flowering chrysanthemum 'Jinba', stem elongation and leafing are rapid in long days, but flower budding and flowering are markedly delayed during winter and spring cut-flower production. Tanigawa et al (2001) and Kunitake et al (2009) reported that to avoid delayed flowering of 'Jinba', the plants must grow at high temperature not in short days (i.e., in the reproductive growth stage) but in long days (i.e. in the vegetative growth stage) for several weeks, or alternatively the mother plants should be grown at high temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the autumn-flowering chrysanthemum 'Jinba', stem elongation and leafing are rapid in long days, but flower budding and flowering are markedly delayed during winter and spring cut-flower production. Tanigawa et al (2001) and Kunitake et al (2009) reported that to avoid delayed flowering of 'Jinba', the plants must grow at high temperature not in short days (i.e., in the reproductive growth stage) but in long days (i.e. in the vegetative growth stage) for several weeks, or alternatively the mother plants should be grown at high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Kunitake et al (2009) have reported in regard to entering 'juvenile phase'; however, there are few reports that about the temperature or period of how long exposure to high temperature is required to pass through the 'juvenile phase'. To avoid delayed flowering of plants, mother plants can be grown in a heated greenhouse to avoid the rosette or juvenile stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A temperatura ambiental pode afetar o período de transição da fase adulta vegetativa para adulta reprodutiva em muitas espécies (BERNIER; PÉRILLEUX, 2005). Por exemplo, curta exposição à temperatura ambiental promove o florescimento em Phalaenopsis (WANG et al, 1995) e Pharbitis (TAKENO et al, 2016), inibindo emChrysanthemum(KUNITAKE et al, 2009) e Arabidopsis thaliana(KIM et al, 2012). Embora o tomateiro floresça de forma autônoma, estudos sugerem que fatores ambientais estejam envolvidos na modificação do padrão de florescimento(SAMACH;LOTAN, 2007).…”
unclassified